Genomic medicine for the paediatrician. Issue 4 (April 2019) - Hastings, Richard; Dixit, Abhijit
Abstract: Genomic medicine is the use of sequence data from an individual's entire genetic code to aid diagnosis and personalise therapeutic options. An important goal of the 100, 000 genomes project in the UK is to embed the infrastructure for the widespread use of whole genome sequencing into the National Health Service. Paediatricians will be at the forefront in using this new technology in the diagnosis of children with multiple congenital anomalies, developmental delay and other suspected genetic conditions. This article provides a description of the basic concepts of genomic medicine. The types of genomic testing that are available are discussed and examples of how genomics is already being used in paediatrics are given. Finally, the challenges for genomic medicine are summarised.